2008
DOI: 10.1901/jeab.2008.90-135
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Partially and Fully Elaborated Generalized Equivalence Classes

Abstract: Most complex categories observed in real-world settings consist of perceptually disparate stimuli, such as a picture of a person's face, the person's name as written, and the same name as heard, as well as dimensional variants of some or all of these stimuli. The stimuli function as members of a single partially or fully elaborated generalized equivalence class when they occasion the mutual selection of each other after the establishment of some subset of relations among the stimuli. Indeed, it is these genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 37 publications
2
14
0
1
Order By: Relevance
“…This variability notwithstanding, the results overall showed that learning baseline relations with 2D stimuli (digital photos) could be followed by emergence of equivalence relations with corresponding 3D stimuli (objects) and other 2D–3D and 3D–2D relational matching (printed photo–object and object–printed photo). Thus, this study contributes substantial new data in support of and extending (i.e., to 3D stimuli) the findings of prior behavior analytic research with normally capable adults (Fields & Moss, ; Fields & Reeve, ; Fields et al, ; Sigurðardóttir, Mackay, & Green, ) to preschool children. The data suggest that equivalence generalization is not restricted by the dimensional nature of the stimuli that are trained during baseline; in other words, perceptual classes (Fields & Reeve, ) may consist of 3D stimuli even when only 2D stimuli are used in baseline training.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This variability notwithstanding, the results overall showed that learning baseline relations with 2D stimuli (digital photos) could be followed by emergence of equivalence relations with corresponding 3D stimuli (objects) and other 2D–3D and 3D–2D relational matching (printed photo–object and object–printed photo). Thus, this study contributes substantial new data in support of and extending (i.e., to 3D stimuli) the findings of prior behavior analytic research with normally capable adults (Fields & Moss, ; Fields & Reeve, ; Fields et al, ; Sigurðardóttir, Mackay, & Green, ) to preschool children. The data suggest that equivalence generalization is not restricted by the dimensional nature of the stimuli that are trained during baseline; in other words, perceptual classes (Fields & Reeve, ) may consist of 3D stimuli even when only 2D stimuli are used in baseline training.…”
Section: Discussionsupporting
confidence: 74%
“…As line lengths increased from 8 to 18 units, the degree of stimulus control over A1 selection decreased, and the participants gradually selected A2 instead of A1. Other studies have also demonstrated this generalization gradient; as physical variations increase, the probability of a variant being included in the equivalence class decreases (Fields & Moss, ; Fields, Reeve, Adams, Brown, & Verhave, ).…”
mentioning
confidence: 83%
“…Tests of emergent relations conducted with matching-to-sample procedures could not reveal such differences: Matching tests can reveal the presence of an emergent relation but not any possible difference in the degree of relatedness. Different degrees of relatedness can be revealed, however, by other measures, such as latency (Fields & Moss, 2008) or transfer of functions (Fields & Watanabe-Rose, 2008). The methodology described here seems to be very sensitive to revealing such effects.…”
Section: Discussionmentioning
confidence: 91%
“…The referents simulated in this study were members of perceptual classes (e.g., Fields & Moss, 2008;. The stimuli designated as A1, A2, and A3 were not individual stimuli; rather, each comprised four pictures of faces, with each face belonging to a different person.…”
Section: Discussionmentioning
confidence: 99%
“…Fields & Moss, 2008). Differences in response to stimuli whose contingent relation is direct or derived might be of relevance in applied settings (e.g., Dymond & Roche, 2009) as well as basic research (e.g., Dymond & Rehfeldt, 2000).…”
mentioning
confidence: 99%